Optimization of a bearing geometry for a cervical total disc replacement - Kölle, Lucia; Flohr, Markus; Pryce, Gregory; Beadling, Andrew R.; Bryant, Michael; Hall, Richard M.; Ferguson, Stephen J.; Helgason, Benedikt (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWhile Total Disc Replacements (TDRs) are generally performing well clinically, reoperation rates indicate that the full potential of the TDR concept might not have been reached. Inspired by the underlying complications related to biomechanics and material longevity that limit the performance of current TDRs, we propose a methodology for the development of TDR-bearings, that addresses such issues.MethodsOur methodology combines finite element model-based optimization with literature derived biomechanical data and an advanced ceramic material to design TDR-bearings. The design optimization aims to functionally replace the structures that are commonly excised (removed) or dissected (cut) during TDR implantation in the anterior column.ResultsThe optimized bearing geometry was able to replicate the moment-rotation curve of the anterior column of the natural C6/C7 level during coupled flexion/extension-anterior/posterior translation movement. Lateral bending and axial rotation were simulated to ensure the TDR would not fail during these load- and motion profiles. Experimental verification of the finite element model showed the suitability of our simulation approach.DiscussionThe combination of computational techniques, advanced materials, and target biomechanical data may allow to overcome limitations of current TDRs and unlock the full potential of the TDR-concept.